RELEVANSI HADIST PILIHAN TERHADAP KENAKALAN REMAJA SAAT KINI DALAM PENDIDIKAN AGAMA ISLAM - Ihza, Muhamad Ihza Pramudya (Amal Insani Foundation, 2025)
Juvenile delinquency is a crime that involves teenagers and not a few also involve children who are still in school. Many factors cause juvenile delinquency to occur, such as lack of attention from parents, teachers and the community so that children feel that this is normal, so it is necessary to provide material on the religious teaching sector such as hadiths to be a signal to prevent juvenile delinquency from occurring. This study uses a qualitative approach with a four-stage method, namely collecting data, reducing data, presenting data and drawing conclusions so that the results of this study present factors and efforts to prevent juvenile delinquency from occurring by presenting hadiths that are relevant to juvenile delinquency.